Social Justice Theories as the Basis for Public Policy on Psychopharmacological Cognitive Enhancement - Elfferich, Astrid (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
Psychopharmacological cognitive enhancements could lead to a higher quality of life of healthy individuals with lower cognitive capacities, but the current regulatory framework does not seem to enable access to this group. This article discusses why Sen’s Capability Approach could open up such access, while two other modern social justice theories – utilitarianism and Rawls’ Justice as Fairness – could not. In short, the utilitarian approach is proven to be inadequate, due to practical reasons and having a low chance of real-world success. Rawls’ Justice as Fairness seems to be problematic because of conflicting stances that follow from his First Principle of Justice. The Capability Approach has the greatest chance of success in the context of these substances, because of arguments that can be identified under the banners of agency/self-respect and the way the public views those who take the capability path out of their poor situation. The article also discusses general and practical problems with psychopharmacological cognitive enhancement that should be addressed when writing new policy on this topic.